2010
DOI: 10.1007/dcr.0b013e3181c703a4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 17,641 Patients With Right- and Left-Sided Colon Cancer: Differences in Epidemiology, Perioperative Course, Histology, and Survival

Abstract: We found that right- and left-sided colon cancers are significantly different regarding epidemiological, clinical, and histological parameters. Patients with right-sided colon cancers have a worse prognosis. These discrepancies may be caused by genetic differences that account for distinct carcinogenesis and biological behavior. The impact of these findings on screening and therapy remains to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

79
494
15
29

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 630 publications
(617 citation statements)
references
References 24 publications
79
494
15
29
Order By: Relevance
“…For colorectal cancer, no significant associations were found between NQO1 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.4.2349 NQO1 C609T Gene Polymorphism andDigestive Tract Cancer: A Meta-analysis C609T polymorphism and colorectal cancer risk, but in the subgroup analysis by ethnicity; significant associations were observed for colorectal cancer in Caucasians, which was similar with previous meta-analysis study (Zhou et al, 2011;Chen et al, 2012). The reason may be that the different cancer sites had a dissimilar prevalence with a difference in clinical feature, prognosis and possibly in genetic and environmental epidemiology (Benedix et al, 2010); and the other reason may be the limited number of studies.…”
Section: Discussionsupporting
confidence: 82%
“…For colorectal cancer, no significant associations were found between NQO1 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.4.2349 NQO1 C609T Gene Polymorphism andDigestive Tract Cancer: A Meta-analysis C609T polymorphism and colorectal cancer risk, but in the subgroup analysis by ethnicity; significant associations were observed for colorectal cancer in Caucasians, which was similar with previous meta-analysis study (Zhou et al, 2011;Chen et al, 2012). The reason may be that the different cancer sites had a dissimilar prevalence with a difference in clinical feature, prognosis and possibly in genetic and environmental epidemiology (Benedix et al, 2010); and the other reason may be the limited number of studies.…”
Section: Discussionsupporting
confidence: 82%
“…5 The vast majority of the body of evidence is based on the leftright dichotomy in outcomes that was proposed over two decades ago. 6 Most of this research was aimed at site-specific (disease-free) survival, baseline characteristics and staging, and only rarely focusing specifically on patterns of metastasis: 7 using this left-right dichotomy, a German multicenter study demonstrated higher rates of pulmonary and liver metastasis in left-sided tumors, 8 on the other hand however, a Japanese study covering a single-center cohort of 820 patients could not identify significant differences in sites of metastasis. 9 There are several possible explanations for the differences in metastatic patterns identified here.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we did survival analysis by cancer type (n=228, cancer type: colorectal adenocarcinoma, cancer type The site and subtype of cancer, and the prognosis of patients depend on gender, stage, race etc [12][13][14][15][16][17]. For these reasons, subgroup analysis is required to identify stage-and genderspecific prognostic genes.…”
Section: Survival Analysis By Mrna or Cancer Typementioning
confidence: 99%